ROLE OF INTERNATIONAL EDUCATIONAL LINKS IN THE FORMATION OF WORLD HIGHER EDUCATION SYSTEM - Rysina, Mariya Yephimovna; Martynenko, Yelena Viktorovna (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
Introduction. Joining Ukraine into European educational space demands the knowledge of the processes going in the sphere of education, in higher education in particular. Higher education is one of the fundamental factors that plays an increasingly important role in the modern world and defines the framework of mankind economic and social progress as a whole and as individual states and peoples. International educational links today are an important and prospective direction of foreign policy of the United States, France, Britain, Germany etc. The special role of education in the modern world is reinforced by the fact that the economic, political and cultural success of the country, the standard of its citizens living depends on the availability of highly qualified specialists. Purpose. To define the role of international educational links in world higher education system development; to characterize their major trends and specific character; to highlight the most significant funds of international cooperation and student exchange programs. Results. International educational links have the following features: 1. World higher education includes many interrelated elements of different levels and nature: these include educational institutions, establishing strong links with foreign partners and organizations, producing a common strategy for the world under the auspices of UNESCO. 2. In the world the higher education has signs of integrity, autonomy in relation to economic, political and other world social systems. The basis for these processes are universal standards of academic freedom and democracy. 3. Well balanced commodity of global system of higher education has a sign assuming the continues development of the higher education system and its adaptation. An important role in this process belongs to an international cooperation and such organizations as UNESCO in particular. International education cooperation has various forms: it may be based on interstate treaties, on the basis of interdepartmental, inter-university disseminated agreements and individual relations. The most common forms of academic exchanges are various mobility programs, scholarships and grants. There is a large number of regional programs, adopted by the UNESCO, EU and other international organizations. Many student exchange programs are currently realized within the European Union (Erasmus Mundus, Socrates). Along with the European student exchange programs there is a large number of academic exchange programmers provided by the United States. The most well-known is the Fulbright program, the FSA program. The most prestigious scholarship program of the UK is Chevening programme (British Chevening Awards). It operates in 150 countries. The British Council supervises the program. It provides an opportunity to obtain a high-quality education in a university of Great Britain, which is chosen by the applicant. It operates in three areas – master’s degree, research, communication experience in a multinational environment. The important role is given to informational and educational agencies. One of the first such organizations was DAAD (German Academic Exchange Service). This self-governing organization unites all German universities and promotes academic cooperation through the exchange of students and scholars. The main DAAD goal is the development of international relations of a higher school of Germany with foreign countries through students and scientists exchange. Conclusion. Ukraine actively participates in international cooperation in the field of education. Nowadays Ukraine has a network of international educational funds which offer additional financing to implement a variety of educational and scientific needs both individual and joint.